2019
DOI: 10.1177/0020764019858651
|View full text |Cite
|
Sign up to set email alerts
|

Mental health stigma among people of color: An examination of the impact of racial discrimination

Abstract: Objective: The primary goal of this study was to examine the relations between racial discrimination experiences and different dimensions of mental health stigma among a diverse sample of people of color. Method: Participants were recruited through blast emails at a large public university and completed an online survey ( N = 205). Four linear regressions were completed predicting from recent racial discrimination experiences to (1) negative beliefs about mental health problems, (2) treatments, (3) treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…In our own research using serial mediation (Hunter et al, 2017), we showed that self-stigma about one’s mental illness or addiction leads to psychiatric symptoms, including depression, that trigger coping responses to reduce self-stigma, such as withdrawal from social supports (Hunter et al, 2017). Building on these studies as well as previous research by Williston et al (2019), in the present study we hypothesize that exposure to race-related stress, operationalized as racial stigma, will trigger internalized self-stigma among adults with a behavioral health disorder (serious mental illness, 2 addiction, or both) to initiate a serial mediation process in which self-stigma leads to depressive symptoms and to increased barriers to help-seeking. Thus, we hypothesize that help-seeking barriers will increase through the serial effect of racial stigma, self-stigma, and depressive symptoms.…”
Section: Study Hypothesesmentioning
confidence: 81%
See 2 more Smart Citations
“…In our own research using serial mediation (Hunter et al, 2017), we showed that self-stigma about one’s mental illness or addiction leads to psychiatric symptoms, including depression, that trigger coping responses to reduce self-stigma, such as withdrawal from social supports (Hunter et al, 2017). Building on these studies as well as previous research by Williston et al (2019), in the present study we hypothesize that exposure to race-related stress, operationalized as racial stigma, will trigger internalized self-stigma among adults with a behavioral health disorder (serious mental illness, 2 addiction, or both) to initiate a serial mediation process in which self-stigma leads to depressive symptoms and to increased barriers to help-seeking. Thus, we hypothesize that help-seeking barriers will increase through the serial effect of racial stigma, self-stigma, and depressive symptoms.…”
Section: Study Hypothesesmentioning
confidence: 81%
“…Gary (2005) first introduced the concept of double stigma as it pertains to help-seeking for persons of color with mental health problems. Williston et al (2019) then demonstrated an empirical relationship between racial discrimination and mental health selfstigma. In the present study, we build on this prior work by examining double stigma in relation to help-seeking barriers for behavioral health services in a sample of Black adults with a behavioral health disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding services offered through online video-guided groups would provide greater accessibility to those who may not traditionally have access mental health resources due to lack of transportation, childcare needs, rurality, or being housebound. Further, people of color, males, and veterans may be deterred from physically accessing mental health services due to societal stigma (Williston et al, 2019). Offering mindfulness interventions through an online platform could alleviate barriers traditionally experienced by populations needing care.…”
Section: Discussionmentioning
confidence: 99%
“…There are several models of racial identity development that can support the psychologist in both navigating their own racial identity development and that of their clients. However, the psychologist is cautioned to ensure identity development is of interest to the client, as historically mental health professionals have pathologized deviations from hegemonic North American culture (Krill Williston et al, 2019). Furthermore, it should be noted that identity models often miss nuances of various intersections of various identities.…”
Section: Best Practices For Collaboration With Clients: Covid-19 Rele...mentioning
confidence: 99%